MODELING THE LINK BETWEEN THE AGRARIAN SECTOR AND THE COUNTRY EXPORT (Multidisciplinary Journal of Science and Technology, 2024)
In this article, we delve into the intricate relationship between the agrarian sector and a country's exports, employing modeling techniques to analyze the dynamics, determinants, and implications of this crucial linkage. Drawing upon a synthesis of economic theory, empirical research, and policy insights, our study aims to shed light on the mechanisms through which the agrarian sector influences a country's export performance and vice versa.